EFFECT OF HYPERTENSION AND THYROID STATUS ON THE EXTRACELLULAR MATRIX AND INTERCELLULAR COMMUNICATION IN THE HEART AND POSSIBILITIES OF PREVENTION WITS OMEGA-3 FATTY ACIDS DIET. (June 2018) - Sykora, M.; Bacova, B. Szeiffova; Soukup, T.; Barancik, M.; Tribulova, N.
Abstract : Objective: Extracellular matrix (ECM) and intercellular communication in the heart can be mainly affected by hypertension. Matrix metalloproteinases (MMP) is responsible for extracellular matrix remodelation what can be subsequently interconnected with disorders of intercellular communication mediated by connexin-43 (Cx43). Alternation of myocardial Cx43 resulted in to develop of malignant arrhythmias. Design and method: In accordance with the European Union Council Directive 86/609/EEC were experiments performed on male 10-month-old wistar euthyroid (EU) rats and hypertensive (SHR) rats with altered thyroid status, which were supplemented with omega-3 fatty acids (PUFA) (200 mg/kg/day) for six weeks. Hypothyroidism (HY) was induced by 0, 05% methimazole and hyperthyroidism (TH) was induced by triiodothyronine (0, 15 mg/kg) applied for two months. Left ventricle tissue was used for molecular analyzes of MMP2, Cx43 and PKCε. Histological analysis of ECM was performed by staining according to van Gieson. Results: Besides thyroid hormones and heart weight reduction, we have found in HY rats decreased expression and activity of MMP2 and elevation of MMP2 activity and expression in SHR HY rats. On the other hand, TH and SHR TH rats with increased heart weight and thyroid hormones and SHR groups did not reveal any changes in MMP2. Expression of Cx43 as well as PKCε, which directly phosphorylate Cx43, was decreased due to hyperthyroidism and increased due to hypothyreoidism. Hypertension did not influences Cx43 and MMP2 in HY and TH rats. The histological staining of collagen in the left ventricle showed a significant increase of collagen in the heart of SHR HY rats. PUFA diet slightly increased the expression and activity of MMP2 in HY rats and decreased activity of MMP2 in the hyperthyroid group. The expression of Cx43 was normalized due to PUFA in HY and TH rats. Conclusions: We can summarize that changes in MMP2 and Cx43 associated with hypertension and altered thyroid status are implicated in the arrhythmogenic mechanism based from the Cx43 alternation after heart remodelation. Short time period of PUFA administration did[Combining Acute Accent]t have significant effect and therefore it would be appropriate to prolong the supplementation time in the future.